Snarf attack, underfoodle, and the secret of life - Amato, Mary.; Long, Ethan (New York : Holiday House, 2017)
Contains three stories in which brothers and best friends Wilbur and Orville Riot catch a thief, overthrow a king, and find a treasure, and includes rules to some of their made-up games.
The Riot Brothers capture a crook -- The Riot Brothers find a hidden treasure -- The Riot Brothers overthrow a king -- Bonus.
3-6
English.
Keywords: Brothers -- Juvenile fiction; Humorous stories; School principals -- Juvenile fiction; Schools -- Juvenile fiction; Brothers -- Fiction; Humorous stories; School principals -- Fiction; Schools -- Fiction; Brothers -- Fiction; School stories; School superintendents and principals -- Fiction; Humorous fiction